The Obligation to Use Bahasa Indonesia in National Trade: A Juridical Review - Zaid zaid; Anggraeni Pratama Indrianto; Fathir Arya Dimas (International Journal of Social Science and Business, 2021)
Language is one of the tools and also a communication system both orally and in writing that is used by certain people in certain countries or regions. Language is a very important essence and a very basic aspect. Therefore, every human being in various activities and life is always closely related to it. This includes trading. Considering that no research discusses the use of Bahasa Indonesia in national trade, especially after passing the omnibus law on job creation, so by using the normative juridical method, this study aims to identify and analyze the need for the use of Indonesian which has emerged as the national language and the ideal official language as part of the from national identity in national trade to achieve fair trade. This research uses a method that is built on a system of norms, rules of laws and regulations, principles, court decisions, agreements, and doctrines (teachings). The results of this study ultimately conclude that the use of Bahasa Indonesia in national trade is mandatory for every party, especially business actors in determining the inclusion of Indonesian on labels of goods and services that are distributed and traded domestically. The results of this study also suggest that every individual and business actor should not forget to include product information in the form of labels using Bahasa Indonesia. Because it can create a “win-win solution” for business actors and their consumers.